Meningkatkan Minat Belajar Siswa Sekolah Dasar dalam Sains Melalui Integrasi Model SAVI-Mind Mapping - Zidane, Mokhammad Rizqi; Putri, Putri Arwinda; Muhlis, M.; Posangi, Nadia Putri Mulyani; Yuliana, Nurma (Nusantara: Jurnal Pendidikan Indonesia, 2025)
Purpose – This study investigates the effectiveness of the SAVI (Somatic, Auditory, Visual, and Intellectual) learning model combined with mind mapping media in enhancing elementary students' interest in science learning. The research addresses common challenges in science education, including limited teaching model variations and students' perceptions of science as a difficult subject.Method – A quasi-experimental design with a quantitative approach was employed. Data was collected through questionnaires and documentation from fourth-grade students at MI Miftahul Huda. Findings – The implementation of the SAVI-mind mapping integration yielded significant positive results. Student responses to the learning model showed 83% positive engagement (strong category) and 43% for negative statements (moderately strong category). Learning interest questionnaires revealed 79% positive responses (strong category) and 55% for negative statements (moderately strong category). Statistical analysis demonstrated a significant influence of the SAVI-mind mapping model on science learning interest, with a sig. value (2-tailed) of 0.000 < 0.05, leading to the acceptance of Ha and rejection of H0. Research Implications – This study provides empirical evidence for the effectiveness of combining kinesthetic, auditory, visual, and intellectual approaches in elementary science education. The findings offer educators a validated teaching model that can be easily implemented in elementary science classrooms. The study provides specific guidelines for integrating SAVI principles with mind mapping techniques, making it invaluable for teachers. This study provides a validated and ready-to-use learning model. They can confidently apply this approach because it is supported by strong empirical evidence. Furthermore, the flexibility of this method allows teachers to make adjustments according to the context and needs of their classrooms.